MORPHOLOGICAL FEATURES OF STENOSIS OF THE TRACHEA AND BRONCHI, BRONCHIOLECTATIC EMPHYSEMA, AND TRACHEOESOPHAGEAL FISTULAS - Polvonnazirova Farangiz Oybek qizi (Modern American Journals, 2025)
Congenital and early developmental bronchopulmonary malformations are frequently characterized by structural defects within the bronchiolar wall, most notably involving the smooth muscle layer. Hypoplasia or aplasia of these muscular elements results in both functional and morphological disturbances, manifesting as abnormal dilatation of the bronchioles. This pathological process plays a critical role in the formation of centrilobular emphysema, particularly in its Leschke variant. Moreover, insufficient maturation of the mucosal lining and smooth muscle framework reduces airway stability, thereby predisposing the respiratory bronchioles to emphysematous transformation.
Keywords: Bronchiolectasis, Leschke emphysema, tracheal stenosis, bronchial stenosis, tracheoesophageal fistula, pathomorphology, airway deformation, respiratory bronchioles, bronchopneumonia.